(untitled) (EDUCATION IN THE 21ST CENTURY, 2024)
The upbringing, training and development of children with visual impairments, preparing them for independent life is the most important problem of special pedagogy, in particular typhlopedagogy. Therefore, many typhlopedagogues and typhlopsychologists have developed special means, methods and conditions for their use to solve many issues of this important problem, including the creation of prerequisites and main directions for the social adaptation of children with visual impairments: complete absence of vision, blind people with residual vision, visually impaired. The present article reveals the challenges of creating the prerequisites for the social adaptation of children with developmental disabilities. The study of this problem is very significant, theoretically, ethically and socially important, as the problems of social adaptation of children with different developmental disabilities are becoming increasingly relevant today. In particular, their social competence, which determines their employment opportunities is essential. It is known, that the key goal and ultimate aim of the upbringing, education and development of children with disabilities is considered to be the preparation of an involved and independent member of ciety, capable of working and operating, to the extent possible. It is therefore practically necessary to create perquisites for the social adaptation of children with different developmental disabilities, which define the practical and theoretical significance of the problem under consideration, in order to solve these problems. It is understood, that developmental disabilities in children result in a breach of relations with society, unity, as a source of growth, according to literature evidence and experience. These children’s underdevelopment of the psyche not only leads to a decline in intellectual abilities, but also affects their ptive capacities. We are therefore interested in how it is possible to establish prerequisites through location that lead to the social adaptation of children with developmental problems. The aim of this analysis - to disclose the key directions for creating the prerequisites for social adaptation of children with developmental disabilities - was defined by the foregoing. The results of studying this problem, the development of a theoretical model and practical approaches for the development of social adaptation in children with visual impairments will allow an effective solution to this problem.